A Framework for Reducing Global Manufacturing Emissions. (June 2016) - Gurtu, Amulya; Searcy, Cory; Jaber, Mohamad Y.
This article establishes outsourcing as a cause of increase in global emissions, presents an original framework to account for greenhouse gas emissions from outsourcing, and recommends a carbon tax on differential emissions between importing and exporting countries. The impact of the carbon tax is shown through examples illustrating the potential financial implications for nations (i.e., the United States, Germany, and China) and an organization heavily engaged in sourcing from energy inefficient nations (i.e., Walmart). The framework provides a basis for developing government policy and assisting corporations in choosing environmentally friendly destinations. The motivation for the research is that current emissions accounting practices are based on places of generation, which provides an incomplete accounting of a nation's emissions inventories and does not provide organizations with insight into the environmental impacts of their offshore operations. The proposed model is transparent, scalable, and relatively simple to implement. The model can provide a basis for improved national policies that will encourage corporations to choose energy-efficient destinations for offshore outsourcing and to help reduce global greenhouse gas emissions.